Controlled growth of in situ silica in a NR/CR blend by a solution sol–gel method and the studies of its composite properties. Issue 66 (19th July 2015) - Bansod, Naresh D.; Kapgate, Bharat P.; Das, Chayan; Basu, Debdipta; Debnath, Subhas Chandra; Roy, Kumarjyoti; Wiessner, Sven
<x xml:space="preserve">Abstract</x> Controlled loading of in situ silica in NR/CR blend by solution sol–gel method for enhancing the reinforcement.